Did Artificial Intelligence Invade Humans? The Study on the Mechanism of Patients’ Willingness to Accept Artificial Intelligence Medical Care: From the Perspective of Intergroup Threat Theory - Zhou, Yuwei; Shi, Yichuan; Lu, Wei; Wan, Fang (Frontiers in Psychology, 2022)
Artificial intelligence (AI) has become one of the core driving forces for the future development of the medical industry, but patients are skeptical about the use of AI in medical care. Based on the Intergroup Threat Theory (ITT), This study verified that patients would regard AI as an external group, triggering the perceived threat of the external group, resulting in avoidance behaviors in the treatment (experiment 1: N=446) and diagnosis (experiment2: N=330) scenarios. The results show that despite AI can provide expert-level accuracy in medical care, patients are still more likely to rely on human doctors and experience more negative emotions as AI is more involved in medical care (experiment 1). Furthermore, patients pay more attention to threats at the individual level, such as realistic threats related to privacy issue and symbolic threats related to the neglect of personal characteristics. In contrast, realistic threat and symbolic threat at the group level had less effect on patients in the medical scenario (experiment 2).